Brown Assessment of Beliefs Scale: A Study of Reliability and Validity - Türkan ÖZCAN; Erkan KURU; Yasir ŞAFAK; M. Emrah KARADERE; K. Fatih YAVUZ; M. Hakan TURKÇAPAR (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Objective: Delusions are fixed wrong beliefs based on false inference and resistant to change. Most prominent featureof delusions is patients have no insight about their delusional belief. Psychiatry benefits from the scales that evaluate thepresence of delusion, the strength of delusion and insight. Out of many scales The Brown Assessment of Beliefs Scale(BABS) is one of the most common scales that used in psychiatry. The aim of our study is to test reliability and validityof BABS’ Turkish version in Turkish population.Method: BABS is translated from English to Turkish by two clinicians and administered to 30 patients with obsessivecompulsive disorder (OCD), and 29 patients with schizophrenia. In order to evaluate inter-rater reliability, BABS wasadministered by two different clinicians. In order to evaluate test- retest reliability, BABS was applied to 57 patientsone week later. To examine BABS Turkish discriminant validity, we used Beck Cognitive Insight Scale, Schedule forAssesing the Three Components of Insight Scale and insight item of Yale-Brown Obsessive Compulsive Scale . In orderto test construct validity, factor analysis was done.Results: Interrater reliability (Kappa =0.54-0.83) and test–retest reliability (r=0.80-0.96, p<0.001) for the total score andindividual item scores was excellent with a high degree of internal consistency (Cronbach alfa=0.90). BABS has strongcorelation with Beck Cognitive Insight Scale (r=-0.84, p<0.001), Schedule for Assesing the Three Components of InsightScale (r=-0.85, p<0.001) and insight item of Yale-Brown Obsessive Compulsive Scale (r=0.67, p<0.001).Conclusion: The data attained from the study of reliability and validity of the scale shows that The Brown Assesment ofBeliefs Scale supports reliability and validity in Turkish population.